MARICHELA SEPE - Planning and Place in the City. Mapping Place Identity (2013) - Balsas, Carlos J.L. (ZARCH, 2015)
MARICHELA SEPEPlanning and Place in the City. Mapping Place Identity Routledge, New York, 2013, 352 p. English